Phenobarbital-Based Protocol for Alcohol Withdrawal Syndrome in a Medical ICU: Pre-Post Implementation Study. (18th April 2023) - Alwakeel, Mahmoud; Alayan, Dina; Saleem, Talha; Afzal, Saira; Immler, Ellen; Wang, Xiaofeng; Akbik, Bassel; Duggal, Abhijit
Abstract : OBJECTIVES: We assessed the efficacy and safety of PB compared with benzodiazepine (BZD)-based protocols in treating AWS in MICU. DESIGN: Single-center, pre-post protocol implementation study. SETTING: The setting is a forty-bed MICU in a tertiary-level academic medical center. PATIENTS: We included all patients admitted to the MICU with a primary diagnosis of AWS. INTERVENTIONS: Intravenous PB 260 mg followed by 130-mg doses every 15–30 minutes as needed up to 15 mg/kg of ideal body weight versus escalating doses of BZD, to achieve a Clinical Institute Withdrawal Assessment Alcohol Scale-Revised score less than 10. MEASUREMENTS AND MAIN RESULTS: ICU and hospital length of stay (LOS), in addition to safety measures were the main outcomes of the study. A total of 102 patients were included, 51 in the PB arm and 51 in the BZD arm. There were no differences in baseline clinical characteristics. Half the patients in each group were admitted with delirium tremens. The use of PB-based protocol was associated with 35% reduction in median ICU LOS (1.5 d [interquartile range, 1.2–2.4 d] vs 2.3 d [1.4–4.8 d]; p = 0.009) and 50% reduction in hospital LOS (3 d [2.7–4 d] vs 6 d [4–10 d]; p < 0.001). After adjustment for comorbidities and clinical factors, PB protocol decreased ICU LOS days by 40% (95% CI; 25.8–53.5%). PB group required fewer adjunctive medications to control symptoms (0.7 [0.5–1] vs 2.5 [2–3]; p < 0.001), less need for intubation (1/51 [2%] vs 10/10 [19.6%]; p = 0.023) and less need for physical restraint (19/51 [37.3%] vs 29/51 [56.9%]; p = 0.047), compared with the BZD group. CONCLUSIONS: A protocol utilizing rapidly escalating doses of PB over a short period is an effective and safe alternative to BZD in treating AWS in MICU.